2022
DOI: 10.1097/apo.0000000000000474
|View full text |Cite
|
Sign up to set email alerts
|

Light Intensity in Nursery Schools: A Possible Factor in Refractive Development

Abstract: Purpose: Increased levels of outdoor light have been found to be associated causally with decreased rates of myopia. The goal of this study was to measure the effect of indoor nursery school light intensity on refraction of preschool children in Israel. Methods: A total of 1596 children aged 4 to 5 years from 27 nursery schools were examined. Light intensity was tested with a luxmeter device (Lux) inside and outside the nursery school. Noncycloplegic refractions were measured with the PlusOptix vision A09 scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Among the associated factors for myopia in the multivariable logistic regression analysis, we were particularly surprised by the markedly lower prevalence of myopia in the participants where classroom curtains were often open. This would be consistent with the light effects reported by Cohen and Iribarren [ 33 ]. The link between light exposure and the prevalence of myopia has not been fully elucidated; however, the proposed reasons include factors such as variations in chromatic light composition, higher light intensities, and increased release of dopamine from the retina, which can slow axial elongation [ 34 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among the associated factors for myopia in the multivariable logistic regression analysis, we were particularly surprised by the markedly lower prevalence of myopia in the participants where classroom curtains were often open. This would be consistent with the light effects reported by Cohen and Iribarren [ 33 ]. The link between light exposure and the prevalence of myopia has not been fully elucidated; however, the proposed reasons include factors such as variations in chromatic light composition, higher light intensities, and increased release of dopamine from the retina, which can slow axial elongation [ 34 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…46 One paper from China has reported major preventive effects of increasing light intensities in classrooms, 47 and one of the papers in this special issue reports on the deleterious effects of low light intensities in kindergarten classrooms. 48 If confirmed, these observations offer some simple interventions to control myopia, ranging from a prototype bright classroom, 49 to systematic upgrades of schoolroom lighting. Light intensity may not be the only important parameter, and a recent paper has reported that repeated exposure to low-level red-light in a clinical situation also has the ability to prevent the progression of myopia.…”
Section: Time Outdoorsmentioning
confidence: 73%
“…The importance of light exposures during time outdoors has revived interest in lighting conditions in schoolrooms 46 . One paper from China has reported major preventive effects of increasing light intensities in classrooms, 47 and one of the papers in this special issue reports on the deleterious effects of low light intensities in kindergarten classrooms 48 . If confirmed, these observations offer some simple interventions to control myopia, ranging from a prototype bright classroom, 49 to systematic upgrades of schoolroom lighting.…”
Section: Increased Understanding Of the Risk Factors For Myopia—the K...mentioning
confidence: 99%
“…7 Much remains unclear about how the retinal image quality is integrated over time into growth signals that may vary locally between different parts of the retina. 334 Here, the environmental luminosity 335 and spatial frequencies 336 play an essential role as the optical quality of a system is best estimated using a brightly lit, high-contrast target.…”
Section: Biphasic Growthmentioning
confidence: 99%